John Macmurray’s Religious Philosophy: What it Means to be a Person. By Esther McIntosh - Patterson, Sue (The journal of theological studies, 2012)
Esther McIntosh has attempted the not insignificant task of reviewing the entire corpus of Macmurray’s work in one volume and in succeeding has rendered a considerable service not only to Macmurray scholars but also to scholarship at large. This work is not merely a careful exposition but also offers a critique which includes the updating of Macmurray’s thought in the light of subsequent developments.